Molecular Links Between Angiogenesis and Neuroendocrine Phenotypes in Prostate Cancer Progression - Wang, Zheng; Zhao, Yicheng; An, Zhiqiang; Li, Wenliang (Frontiers in Oncology, 2020)
Androgen deprivation therapy (ADT), a major treatment for prostate cancer, is initially effective for the majority of patients. However, prolonged ADT promotes drug resistance and progression to an aggressive variant with reduced androgen receptor signaling, so called neuroendocrine prostate cancer (NEPC). NEPC is lethal, poorly understood, and without effective treatment. Elevated expression of neuroendocrine markers and increased angiogenesis are two prominent phenotypes of NEPC. Several studies have shown a positive correlation between these two characteristics and poor clinical-pathological parameters. However, direct molecular links between the two phenotypes in NEPC and their mechanisms remain largely unclear. Their elucidation should substantially expand our knowledge in NEPC. This knowledge, in turn, would facilitate the development of effective NEPC treatments. We recently showed that a single critical pathway regulates both ADT-enhanced angiogenesis and elevated expression of neuroendocrine markers. This pathway consists of CREB1, EZH2, and TSP1. Here we seek new insights to identify molecules common to pathways promoting angiogenesis and neuroendocrine phenotypes in prostate cancer. To this end, our focus is to summarize the literature on proteins reported to regulate both neuroendocrine marker expression and angiogenesis as potential molecular links. These proteins, often described in separate biological contexts or diseases, include AURKA and AURKB, CHGA, p53, RB1, GRK3, CREB1, EZH2, MYCN, HIF1, FOXA2, ONECUT2, IL-6 and RET. We also present the current efforts in prostate cancer or other diseases to target some of these proteins, which warrants testing for NEPC, given the urgent unmet need in treating this aggressive variant of prostate cancer.